2020
DOI: 10.1007/s41999-020-00414-y
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the physical activity levels of acutely ill older adults in Hospital At Home settings: an under-researched field

Abstract: Purpose The purpose of this review was to identify, evaluate and synthesise existing evidence reporting the physical activity levels of acutely ill older patients in a ‘Hospital At Home’ setting and compare this to patients with similar characteristics treated in a traditional hospital inpatient setting. Functional changes and any adverse outcomes due to physical activity (e.g. falls) in both settings where PA was reported or recorded were also evaluated as secondary outcomes. Methods A search strategy was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
2
7
0
1
Order By: Relevance
“…However, they found that the same population treated in-hospital spent 6.6% of their day active and performed only 882 daily steps, placing them at an increased risk of functional decline. 16 These results and our findings support the hypothesis that the incidence of posthospital syndrome and ‘pathological inactivity’ is likely to be lower among home-treated patients than in hospitalised patients, and this can potentially impact the patients’ recovery and readmission rates.…”
Section: Discussionsupporting
confidence: 88%
“…However, they found that the same population treated in-hospital spent 6.6% of their day active and performed only 882 daily steps, placing them at an increased risk of functional decline. 16 These results and our findings support the hypothesis that the incidence of posthospital syndrome and ‘pathological inactivity’ is likely to be lower among home-treated patients than in hospitalised patients, and this can potentially impact the patients’ recovery and readmission rates.…”
Section: Discussionsupporting
confidence: 88%
“…A recent systematic review seeking to investigate if geriatric inpatients >60 years old receiving acute care in a home-based setting are more active than hospital-based patients identified that there was a complete absence of studies designed to answer this question. 43 The present study, although in the rehabilitation setting, is the first to provide evidence for higher physical activity in homebased geriatric inpatients and thus gives incentive for future research in a larger sample.…”
Section: Discussionmentioning
confidence: 70%
“…4 Even in those who ambulate independently, high sedentary time and low levels of physical activity during hospitalisation is common, [5][6][7] with an estimated 87-100% of time spent sitting or lying in bed 8 and a daily average of only 880 steps. 9 These patterns are similar even in inpatient settings where the purpose of admission is to optimise recovery, such as rehabilitation. Adults and older adults in inpatient rehabilitation are typically inactive [10][11][12][13][14][15][16][17][18][19][20] and have high levels of sedentary time [14][15][16]18,[21][22][23] which are associated with adverse outcomes including functional decline and hospital-acquired disability.…”
Section: Introductionmentioning
confidence: 97%